Social infrastructure planning in declining rural centres - Jaak Kliimask; Garri Raagmaa (European Regional Science Association (ERSA), 2004)
The aim of this empirical contribution is to analyse social infrastructure (SI) planning and development practices in Estonian local communities. The SI considered: schoolhouses, kindergartens, sports halls, cultural houses and the like, were extensively built by collective farms and local enterprises during the 1970s and 1980s. During the post-socialist transition period, spatial structures have gone through drastic changes. Especially remote rural and old industrial areas lost a major part of their employment and remarkable share of population. The SI facilities are partly out of use because of low demand and high operation costs, simultaneously, they would need remarkable investments to be renovated and upgraded. This paper consists of three principal parts. First, we analyse a historical development of planning practices in the Soviet Union and its consequences to the settlement structure. Secondly, we present an ad hoc typology and genesis of rural settlements and service centres; using census data, we describe their socio-economic and demographic (social) transition of the 1990s. Finally, we analyse comparatively the problems and planning practices of SI in selected communities.
Keywords: 330